Book Notices - Dandelion, Pink (Quaker studies, 2003)
Jone Salomonsen, Enchanted Feminism: ritual, gender and divinity among the Reclaiming witches of San Francisco; Susan V. Hartshorne, Chair of Compiling Committee. 100 years in New Earswick: A centenary history in pictures; Howard Brinton, with historical update and notes by Margaret Hope Bacon. Friends for 350 years.